2015
DOI: 10.1111/evj.12530
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal chromatolysis in the subgemmal plexus of gustatory papillae in horses with grass sickness

Abstract: While identification of chromatolytic subgemmal neurons in post mortem samples correctly differentiated EGS and control horses, further study is required to evaluate this technique for premortem EGS diagnosis. Equine grass sickness represents a spontaneous model of subgemmal neuronal chromatolysis that facilitates study of the pathology of structures involved in taste.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Histology of tongue papillae in the diagnosis of EGS has also been investigated, with McGorum and others (2016) comparing levels of neuronal degeneration between EGS cases and control postmortem samples. This study reported 100 per cent sensitivity and 98 per cent specificity in differentiating EGS cases from controls.…”
Section: Advances In Antemortem Diagnosismentioning
confidence: 99%
“…Histology of tongue papillae in the diagnosis of EGS has also been investigated, with McGorum and others (2016) comparing levels of neuronal degeneration between EGS cases and control postmortem samples. This study reported 100 per cent sensitivity and 98 per cent specificity in differentiating EGS cases from controls.…”
Section: Advances In Antemortem Diagnosismentioning
confidence: 99%
“…Retrospective application of this approach yielded 100% sensitivity and specificity Requires prospective validation Histopathology of gustatory papillae [60] Retrospective application of this approach yielded 100% sensitivity and high specificity (98%) Requires prospective validation Ancillary diagnostic tests can also be applied to specifically exclude other differential diagnoses.…”
Section: Identification Of Ans And/or Ens Dysfunctionmentioning
confidence: 99%
“…The paper by McGorum et al [1] in the current issue describes the optimal diagnostic sensitivity and high diagnostic specificity associated with the histopathological examination of gustatory papillae in EGS cases. Despite the consensus that histopathological identification of chromatolytic autonomic neurons represents the gold standard diagnostic test, the applicability of this approach in the clinical case is hampered by the antemortem inaccessibility of tissue with sufficiently large clusters of autonomic neuronal cell bodies, thus necessitating relatively costly and invasive procedures such as laparotomy or laparoscopy.…”
Section: Introductionmentioning
confidence: 99%